MANAGEMENT OF STUDENT DEVELOPMENT IN THE DEVELOPMENT OF NON ACADEMIC ACHIEVEMENT IN SENIOR HIGH SCHOOL - Aqsal Rizky Ramadhan; Sujarwo Sujarwo; Muh Khamid (Jurnal Eduscience)
Purpose-The importance of managing student development to develop non-academic achievements, which are often less noticed than academic achievements. The increasing demands of society for diverse skills, good management of student development becomes an urgent need to support students' potential optimally. This study aims to analyze the management of student development in the development of non-academic achievement, including planning, organizing, actuating, and controlling.